Application of water borne paint on the tractor chassis. Issue 1 (June 2015) - Kang, H C; Cai, A K; Bi, R; Wang, B; Ma, C Q; Yan, L F; Liu, X; Zhang, B B; Shi, X Y
Abstract: This paper introduces the test and application of cleaner water borne paint coating mode on great wheel tractor chassis.